(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
This Paper examines the existing spatial inequalities in residential areas of Dhaka City, the megacity of Bangladesh on the basis of household resources and amenities. The empirical data has been collected through a detailed semi-structured questionnaire from 180 purposively selected respondents in Dhanmondi and Mirpur residential area and Kallayanpur slum area. . The results clearly indicate that there exist significant differences and variations of household resource and amenity indicators, particularly household and housing characteristics, sanitation facilities, water, electricity, and gas supplies, etc. More specifically, the finding reveals that there is a huge gap in tenure systems, income-expenditure, occupational, education and social status, utilities, and physical developments, and these are the prime issues for creating massive inequality in slum area from other residential areas. Furthermore, the slum dwellers are more deprived and neglected from all kinds of urban facilities though they play significant role in informal economy of urban areas as well as in GDP of Bangladesh. Hence, the findings suggest that policymakers should take proper initiatives to address multi-dimensional issues of slum areas to ensure a sustainable environment among residential areas of Dhaka City. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(1), 2020, P 49-62